Pengaruh Kualitas Pelayanan, Fasilitas Hotel dan Harga Terhadap Kepuasan Konsumen Di Hotel Noormans Semarang - Muhammad Noor Cholis; Enik Rahayu; Renny Apriliyani; Susmono Widagdo; Henry Yuliamir (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia, 2023)
The purpose of this study is to determine the effect of service quality, hotel facilities and prices on customer satisfaction at Hotel Noormans Semarang. Research data obtained through documentation and questionnaires. The sample used in the study was 125 respondents. The data obtained were processed using descriptive analysis and quantitative statistical analysis. The data analysis technique used is multiple linear regression analysis, model testing and hypothesis testing. The results of the analysis show that partially and simultaneously the variables of service quality, hotel facilities and prices affect customer satisfaction at Noormans Hotel Semarang